Studies on the mouldability of structural foams in hybrid moulds - Nogueira, A. A. (2013)
In the context of the research project Hybridmould 21, studies on the mouldability of structural foams using hybrid moulds have been carried out. Hybrid injection moulds are an increasingly considered alternative for prototype series or short production runs of large dimension parts. In this solution for injection moulds the moulding elements (blocks or other inserts) are manufactured in alternative metallic materials or in synthetic materials typically using rapid prototyping techniques. Structural foams, known since the 70s, are moulded by injection moulding without using the high pressures typically used in injection moulding. The formation of the structural foam results from the dispersed gaseous phase, which derives from the expansion of a chemical blowing agent usually compounded in a compatible masterbatch. In this project various thermoplastics and thermosets were used, namely, PP, ABS and PUR, us-ing a hybrid mould instrumented for the monitoring of temperature, pressure and expansion force. The mould-ing block was manufactured by vacuum casting of an epoxy composite. In this paper are mainly discussed the results obtained on liquid injection moulding polyurethane resins in the hybrid mould.